Utilization of Geographic Information System for hydrological analyses: A case study of Karbala province, Iraq - Maarez, Habeeb Ghdhaib; Jaber, Hussein Sabah; Shareef, Muntadher Aidi (Iraqi Journal of Science, 2022)
Analyses are the power point of GIS because GIS can process and analyze different spatial and attribute data, leading to new results for supporting decision makers. The research aims to study advanced hydrologic analyses for the western part of Karbala province, Iraq. The hydrologic analysis is done based on where that DEM creates from the field survey method. This analysis gives digital maps and tables showing the region’s main and minor hydrological properties, such as flow direction, flow accumulation, stream order, stream to feature, basin, and watershed maps. Also, it can be calculated as area, perimeter, lengths of streams, and numbers of stream orders for the main watersheds that are effective in the study area. These analyses are very important for making decisions in studying the hydrologic properties of any region in Iraq, and the GIS technique saves time, cost, and effort.